"Burning money" and institutional decline during Zimbabwe's hyperinflation. Issue 48 (14th October 2022) - Miller, Stephen Matteo; Ndhlela, Thandinkosi
ABSTRACT: During Zimbabwe's hyperinflation that ended in 2009, people turned to an illegal round-tripping transaction called 'burning money' to preserve purchasing power. The transaction involved illegally acquiring foreign currency at the official rate before converting back to domestic currency in the black market. After computing the widely used 'Old Mutual' parallel market rate from the ratio of prices of Old Mutual shares, which traded in London and Harare, we use the daily parallel market and official exchange rate data from 1999 to 2008 to estimate the monthly value of 'burning money'. While arguably vital, as the transactions were optional, we value them using a single-factor call exchange option formula, which accounts for the volatility of official and parallel market exchange rates and systematic parallel market risk and compare it to changes in the parallel market premium, often used to measure non-unified exchange rates. The 'burning money' option values exceed changes in the parallel market premium and respond more to institutional decline, measured using the cash component of M2 equal to one minus the non-cash component of M2 known as Contract Intensive Money, and especially political risk.